Efficiency Comparison of Asynchronous and Synchronous Buck Converter with Variation in Duty Cycle and Output Current - Ralfi Wibowo Rachmad; Tomy Abuzairi (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
There are two most commonly used topologies in buck converter applications, asynchronous and synchronous buck converter. These two topologies have its own advantages and disadvantages from a performance point of view. The difference in performance, especially in the aspect of efficiency need to be addressed further, knowing the efficiency is a crucial aspect of buck converter application. In this study, the comparison of asynchronous and synchronous topology in terms of its efficiency will be analyzed using software simulation and hardware prototypes. Software simulation will be used to validate the workings of buck converter prototypes by comparing its characteristics against the hardware prototypes. Furthermore, the performance between both topologies will be analyzed under various operating conditions. Based on the results obtained in this study, when the applied duty cycle is low, for instance in 30% duty cycle and both converters operate at the lowest current, the asynchronous topology have a better efficiency of 19.15% against the synchronous topology, however, when both converters operate at the highest current, the synchronous topology shows its efficiency advantage of 6.56% against the asynchronous topology. On the other hand, in a higher duty cycle operation, for example in 80% duty cycle, both converters have an insignificant difference of efficiency.